2008
DOI: 10.1080/00036840600771239
|View full text |Cite
|
Sign up to set email alerts
|

The labour market impact of body weight in China: a semiparametric analysis

Abstract: While a positive wage effect of Body Mass Index (BMI) is widely observed in low-income developing countries, a negative wage effect of BMI is often observed in high-income developed countries. To fill the gap between these previous findings, we investigate the relationship between body weight and wages in transition economies. We focus on China, whose rapid economic growth of the 1990s was followed by a rapid increase in overweight and obesity while still experiencing significant food insecurity and underweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…that are unrelated to BMI and then provide a local linear regression estimate showing the relationship of this residual to BMI itself. We estimate confidence intervals using the "wild" bootstrap algorithm outlined by Yatchew (1998, 688) and Yatchew (2003, 160ff (Shimokawa 2008;Yatchew 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…that are unrelated to BMI and then provide a local linear regression estimate showing the relationship of this residual to BMI itself. We estimate confidence intervals using the "wild" bootstrap algorithm outlined by Yatchew (1998, 688) and Yatchew (2003, 160ff (Shimokawa 2008;Yatchew 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Even more recent has been the adoption of semiparametric methods. Shimokawa (2008) used data from China to estimate semiparametric models and fi nds that wages are lower for men and women in the tails of the BMI distribution. Kline and Tobias (2008), using data from the 1970 British Cohort study, found that marginal increases in BMI are most harmful for men who are overweight or obese and for women in the "healthy" weight range.…”
mentioning
confidence: 99%
“…The third is studies examining the changing role of Party membership in obtaining elite occupations and other benefits (Li & Walder, 2001;Walder, 1995). The fourth is studies examining the economic returns to physical appearance in the Chinese labor market, including height (Gao & Smyth, 2010) and weight (Shimokawa, 2008).…”
Section: Chinese Context and Existing Literaturementioning
confidence: 99%
“…Returns to human capital have increased over the market reform period (Gao & Smyth, 2015). Studies have identified that physical appearance captured by beauty (Hamermesh et al, 2002), height (Gao & Smyth, 2010) and weight (Shimokawa, 2008) earn economic rents/penalties. While the market has increased in importance in the allocation of resources, the wage premium from being a Party member has not declined.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation